2008
DOI: 10.1371/journal.pgen.1000201
|View full text |Cite
|
Sign up to set email alerts
|

FtsK-Dependent Dimer Resolution on Multiple Chromosomes in the Pathogen Vibrio cholerae

Abstract: Unlike most bacteria, Vibrio cholerae harbors two distinct, nonhomologous circular chromosomes (chromosome I and II). Many features of chromosome II are plasmid-like, which raised questions concerning its chromosomal nature. Plasmid replication and segregation are generally not coordinated with the bacterial cell cycle, further calling into question the mechanisms ensuring the synchronous management of chromosome I and II. Maintenance of circular replicons requires the resolution of dimers created by homologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
140
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(145 citation statements)
references
References 41 publications
5
140
0
Order By: Relevance
“…S4). In similar experiments with tandem dif plasmids, dif/dif HJs were never detected, suggesting that they were more efficiently processed into product and/or back into substrate than attP TLC /dif1 HJs (5,20). Impeding XerD strand exchanges entirely abolished HJ and product formation, confirming that attP TLC /dif1 recombination was initiated by XerD catalysis (Fig.…”
Section: Quantity Of Xerc and Xerd Is A Limiting Factor Of Tlcϕ Integmentioning
confidence: 57%
See 1 more Smart Citation
“…S4). In similar experiments with tandem dif plasmids, dif/dif HJs were never detected, suggesting that they were more efficiently processed into product and/or back into substrate than attP TLC /dif1 HJs (5,20). Impeding XerD strand exchanges entirely abolished HJ and product formation, confirming that attP TLC /dif1 recombination was initiated by XerD catalysis (Fig.…”
Section: Quantity Of Xerc and Xerd Is A Limiting Factor Of Tlcϕ Integmentioning
confidence: 57%
“…In V. cholerae, as in most bacteria, the Xer machinery consists of two tyrosine recombinases, XerC and XerD. They act at a unique specific chromosomal site, dif, on each of the two circular chromosomes, chrI and chrII, of the bacterium (5). Integrative mobile elements exploiting Xer (IMEXs) carry a dif-like site on their circular genome, attP (3,4) (Fig.…”
mentioning
confidence: 99%
“…Instead, it has been shown that the El Tor variant of CTXϕ hijacks XerC and XerD, two host-encoded tyrosine recombinases that normally function to resolve chromosome dimers (5), to integrate at dif1, the dimer resolution site of the larger of the two V. cholerae chromosomes (6). Xer recombination sites consist of binding sites for XerC and XerD, separated by a 6-bp to 8-bp overlap region; strand exchanges occur at the border of this region (7).…”
mentioning
confidence: 99%
“…In Escherichia coli, XerCD proteins bind and catalyze recombination at homologous 28-bp dif sites, composed of two 12-bp binding sites for XerC and XerD separated by a 6-bp spacer or overlap region, which allows for XerC-XerD interactions that ensure stable synapsis (10,11). Because V. cholerae harbors two distinct, nonhomologous circular chromosomes (chromosome I and II) (12,13), two dif sites are present, dif1 in chromosome I and dif2 in chromosome II (9); similar to E. coli, the same FstKdependent mechanism coordinates dimer resolution on each chromosome with cell division (14). The dif1 site differs from dif2 at four polymorphic sites, one of which is located in the XerC binding site and the other three sites are located in the 6-bp spacer region (9,14).…”
mentioning
confidence: 99%
“…Because V. cholerae harbors two distinct, nonhomologous circular chromosomes (chromosome I and II) (12,13), two dif sites are present, dif1 in chromosome I and dif2 in chromosome II (9); similar to E. coli, the same FstKdependent mechanism coordinates dimer resolution on each chromosome with cell division (14). The dif1 site differs from dif2 at four polymorphic sites, one of which is located in the XerC binding site and the other three sites are located in the 6-bp spacer region (9,14).…”
mentioning
confidence: 99%